Antioxidant activity of indigenous yeasts isolated during the fermentation of table olives from Northeast of Portugal - Oliveira, Tatiane C.G. (2016)
Yeasts have an important role in fermented foods, including table olives. These microorganisms can be a new source of natural antioxidants. Free-radical-scavenging antioxidants have potential as protective agents against various degenerative diseases caused by oxidative damage. In the present study, antioxidant activity of indigenous yeasts isolated during the natural fermentation of table olives (Negrinha Freixo cv.) was evaluated. These strains were previously identified by rDNA sequences of the ITS region. The antioxidant activity was performed by the percentage of reduction of the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. The studied strains are included in the genera Saccharomyces, Candida, Pichia, Debaryomyces, Rhodotorula and Galactomyces. Saccharomyces boulardii was included as probiotic reference strain. All strains showed distinct antioxidant activity. The ability to scavenge DPPH radical indicated that S. cerevisiae isolated from table olives may be a promising candidate strain for use as probiotics with antioxidant activity.